Advanced Organic Molecular Doping Applied to Si: Influence of the Processing Conditions on the Electrical Properties. Issue 14 (25th June 2018) - Caccamo, Sebastiano; Grimaldi, Maria Grazia; Italia, Markus; La Magna, Antonino; Mannino, Giovanni; Puglisi, Rosaria A.
Abstract : The molecular doping (MD) process consists of depositing a molecular precursor on a silicon substrate, covering the precursor with a cap layer and annealing the sample to decompose the precursor and diffuse dopant atoms within Si. In the literature, preliminary results have shown that dopant diffusion inside a substrate correlates with the presence or absence of the cap layer. The purpose of this work is to study how the cap coating changes the doping process and efficiency. The authors investigate and compare the electrical properties of silicon samples after MD doping with three different cap layers and without a cap layer. The authors examined a 500‐nm‐thick layer of SiO2 deposited by spin‐on‐glass (SOG), a 500‐nm‐thick layer of SiO2 deposited in a chemical vapor deposition (CVD) chamber at room temperature and a 100‐nm‐thick layer of oxidized silicon placed over and in contact with the samples to be doped. Spreading resistance profiling (SRP) measurements are then performed on these samples to monitor important doping features, such as carrier dose, carrier concentration, sheet resistance and junction depth, obtained with different capping conditions. Abstract : Si is immersed in an organic molecular solution to form a monolayer of P precursors on the sample surface which will be then diffused to work as dopants. Sample is then covered with a cap layer to avoid loss of the molecules during the diffusion step. The cap layer type plays an important role on the final electrical characteristics of the doped sample.